Biphasic intra-thoracic pressure regulation augments cardiac index during porcine peritonitis: a feasibility study. (January 2014) - Cinel, Ismail; Goldfarb, Roy D.; Metzger, Anja; Lurie, Keith; Jasti, Purnachandra; Knob, Christopher R.; Parrillo, Joseph E.; Phillip Dellinger, R.
Abstract Preservation of cardiac output (CO) and pulmonary artery pressure (PAP) is vital to maintaining tissue oxygenation in sepsis. This feasibility study tested the hypothesis that therapeutic intra-thoracic pressure regulation (tIPR), delivered with a novel device, was designed to non-invasively enhance venous return by creating sub-atmospheric intra-thoracic pressure during the expiratory phase of mechanical ventilation, improves CO without fluid resuscitation in a porcine E. coli peritonitis model of sepsis. Seven pigs were intubated, anaesthetized and instrumented with a Swan-Ganz and femoral artery catheter. After a 30 min basal period, a fibrin clot containing 4–5 × 109 cfu kg−1E. coli O111.B4 was implanted in the peritoneum. One hour after clot implantation, tIPR was utilized for 30 min and then removed from the ventilator circuit for 30 min. This tIPR cycle was repeated 4-times. Changes in haemodynamic parameters were calculated by comparing pre-tIPR values to peak values during tIPR administration. Following peritonitis, tIPR significantly increased the peak cardiac index (mean ± SEM) (14.8 ± 2.6 vs 7.9 ± 2.3 ml kg−1) and mean arterial pressure (10.2 ± 1.5 vs 4.9 ± 1.1 mmHg) and simultaneously decreased PAP (−7.7 ± 1.5 vs −2.7 ± 0.8 mmHg). These results support the feasibility of the concept that therapeutic application of negative expiratory pressure may provide a non-invasive and complementary approach to increase cardiac output and organ perfusion in the setting of septic shock.